Peroxisome proliferator-activated receptors regulate the progression and treatment of gastrointestinal cancers - Zhang, Min; He, Shujie (Frontiers in Pharmacology, 2023)
Peroxisome proliferator-activated receptors (PPARs) are essential nuclear hormone receptors regulating the metabolic processes, and participate in the initiation and progression processes of tumors. Gastrointestinal (GI) cancer is a kind of prevalent malignancy worldwide that originate from the tissues of gastrointestinal tract, characterized by severe symptoms and poor prognosis. Numerous published studies have concentrated on the investigation of the critical role of PPARs in esophageal cancers, gastric caners and colorectal cancers. Here, we summarize and review the current papers to understand the role of PPARs in the pathogenesis of the GI cancers to provide a systematic reference for the following related investigation and development of efficient therapies targeting PPARs and pathways.